The Problem of Oligopoly - Wolfe, J. N. (Review of Economic Studies, 1953)
Journal Article The Problem of Oligopoly Get access J. N. Wolfe J. N. Wolfe Toronto Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 21, Issue 3, 1953, Pages 181–192, https://doi.org/10.2307/2295771 Published: 01 January 1953